Faces of joblessness in Switzerland A people-centred perspective on employment barriers and policies - Georgieff, Alexandre (OECD Social, Employment and Migration Working Papers, 2024)
Open unemployment and joblessness in Switzerland are low compared to OECD standards. Yet a comparatively high proportion of working-age individuals remain weakly attached to the labour market, with unstable jobs, or with limited working hours. As an initial step towards a possible in-depth project, this Faces of Joblessness feasibility study provides insight into the nature and incidence of the structural barriers that are likely to prevent individuals from fully engaging in employment and speculates on their possible links with underutilized employment potential. It shows that lack of recent work experience and substantial non-labour or partner income are two key employment barriers in Switzerland. Partner income can be a barrier for women in particular and might be one of the reasons why many women leave stable employment at childbearing age, alongside low supply and high cost of early childhood education and care programs. Workers over 60 also represent a significant underutilized employment potential, as many have taken early retirement. Non-EU migrant are particularly exposed to potential labour market difficulties at younger age, and many of them have low levels of education, poor professional skills or limited work experience. This study also suggests that many jobless are confronted with complex and inter-related employment obstacles